Bacillus enclensis sp nov., isolated from sediment sample - Dastager, Syed Gulam; Mawlankar, Rahul R.; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Ramana, V. Venkata; Shouche, Yogesh S. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A novel bacterial strain, designated SGD-1123(T) was isolated from Chorao Island, in Goa Province, India. The strain was found to be able to grow at 15-42 A degrees C, pH 5-12 and 0-12 % (w/v) NaCl. The whole cell hydrolysates were found to contain meso-diaminopimelic acid, galactose and arabinose. The major fatty acids were identified as iso-C-15:0 and anteiso-C-15:0, MK-7 was identified as the predominant menaquinone and the predominant polar lipids were identified as diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an unidentified aminolipid. The genomic DNA G+C content was determined to be 44.6 mol%. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and further revealed that strain SGD-1123(T) had highest sequence similarity with Bacillus aquimaris, and forms a separate clade with its closest relatives i.e. B. aquimaris, Bacillus vietnamensis and Bacillus marisflavi, with which it shares 94.5, 94.1 and 94.1 % similarity respectively. The phylogenetic, chemotaxonomic and phenotypic analyses indicated that strain SGD-1123(T) represents a novel species within the genus Bacillus, for which the name Bacillus enclensis is proposed. The type strain is SGD-1123(T) (NCIM 5450(T)=CCTCC AB 2011125(T)).
Keywords: Bacillus sp; Marine sediment; Polyphasic

Bacillus filamentosus sp nov., isolated from sediment sample - Sonalkar, Vidya V.; Mawlankar, Rahul R.; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S.; Dastager, Syed Gulam (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel Gram-stain positive, endospore-forming bacterium, designated SGD-14(T), was isolated from a marine sediment sample in Goa Province, India. Cells of the isolate were found to be strictly aerobic. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain SGD-14(T) showed a similarity of 99.5 % with Bacillus endophyticus and similarities to other Bacillus type strains were below 96 %. The whole-cell sugar pattern was found to consist of ribose, xylose and glucose. The predominant menaquinone was identified as MK-7 and the major fatty acids as anteiso-C-15:0, iso-C-15:0, iso-C-16:0, anteiso-C-17:0, C-16:0 and iso-C-14:0. The strain was found to grow optimally at 30 A degrees C and pH 7.0-7.5. DNA G + C content was determined to be 39.6 mol%. The phospholipid pattern was found to consist of diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. DNA-DNA hybridization studies between strain SGD-14(T) and B. endophyticus CIP106778(T) showed that strain SGD-14(T) exhibited < 70 % similarity with B. endophyticus CIP106778(T). Differences in phenotypic and chemotaxonomic characteristics between the novel strain and B. endophyticus CIP106778(T) further confirmed that this isolate represents novel species. Phylogenetic analysis showed that strain SGD-14(T) fits in the same clade with B. endophyticus with 100 % bootstrap values. Strain SGD-14(T) is therefore considered to represent a novel species of the genus Bacillus, for which the name Bacillus filamentosus sp. nov. is proposed. The type strain of Bacillus filamentosus is SGD-14(T) = (=NCIM 5491(T) = DSM 27955(T)).
Keywords: Bacillus; Filaments; Polyphasic; Sediment